New graphene nanocomposites-based adsorbents - Badiei M.; Asim N.; Mohammad M.; Alghoul M.; Samsudin N.A.; Akhtaruzzaman M.; Amin N.; Sopian K. (Elsevier, 2023)
Graphene-based materials with unique mechanical, chemical, and biological properties are important members of the carbon family and important materials in the fields of nanomaterials and nanotechnology for molecular sorption and separation. The most common graphene materials that have been widely studied are graphene, graphene oxide (GO), reduced graphene oxide (rGO), and graphene nanocomposites. Because of extensive research, significant development has been made in the preparation, synthesis, and modification of these materials that have been commonly introduced as effective adsorbents of organic and inorganic toxic contaminants. The accumulation of pesticides, herbicides, and pharmaceuticals, as well as dyes and heavy metals from municipals and industrial discharges and their by-products, can release hazardous compounds into water resources and the atmosphere. The adsorption of toxic pollutants and contaminants onto graphene-based nanomaterials have been widely investigated. Recent studies revealed that graphene, GO, rGO and their modified nanocomposites are potential adsorbents. Employing novel efficient graphene-based adsorbents have opened a venue to sustainable green remediation. This chapter discusses the latest graphene-based adsorbents fabricated for removal of varieties of contaminants and toxic solid and gaseous materials. Additionally, the significant effect of surface functionalization of these adsorbents was also studied. 2021 Elsevier Inc. All rights reserved.